1969
DOI: 10.1007/bf02531055
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of α‐tocopherol to α‐tocopheryl quinone by carbon tetrachloride‐ethanol solvent

Abstract: The addition of small amounts of CCl4 to ethanolic solutions of α‐tocopherol, vitamin A acetate or β‐carotene caused destruction of these fat‐soluble compounds. The oxidation product of α‐tocopherol was identified as α‐tocopheryl quinone by UV and IR spectral analysis. Maximum conversion to the quinone occurred with a ratio of CCl4 to ethanol of 25∶75 (v/v).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Tocopherols seemed also to influence other important biophysical membrane characteristics, such as fluidity, in a manner similar to that of cholesterol. Studies of the antioxidant properties led to the recognition that during the reaction of α-tocopherol with an appropriate oxidizing species, α-tocopherol may be oxidized to α-tocopheryl quinine (Seward et al, 1969). In latter studies where peroxidizing lipids were used to induce the formation of antioxidant radicals, electron spin resonance spectroscopy revealed that free radical interactions of dl-α-tocopherol generate dl-α-tocopheroxyl radicals.…”
Section: α -Tocopherol: Riding the Wave For Five Decadesmentioning
confidence: 99%
“…Tocopherols seemed also to influence other important biophysical membrane characteristics, such as fluidity, in a manner similar to that of cholesterol. Studies of the antioxidant properties led to the recognition that during the reaction of α-tocopherol with an appropriate oxidizing species, α-tocopherol may be oxidized to α-tocopheryl quinine (Seward et al, 1969). In latter studies where peroxidizing lipids were used to induce the formation of antioxidant radicals, electron spin resonance spectroscopy revealed that free radical interactions of dl-α-tocopherol generate dl-α-tocopheroxyl radicals.…”
Section: α -Tocopherol: Riding the Wave For Five Decadesmentioning
confidence: 99%
“…and C-7 relative to those in Table II references therein]; and it can be generated by reaction of EH with the hepatotoxin CCI 4 [102] and during oxidation of EH with NO 2 [103]. Vitamin E has been proposed to protect lung tissue from damage by NO 2 in polluted air by reaction to form this quinone [74].…”
Section: A Formation Of the ~-Tocopheroxyl Radicalmentioning
confidence: 99%